Emergence in Vietnam of Streptococcus pneumoniae resistant to multiple antimicrobial agents as a result of dissemination of the multiresistant Spain(23F)-1 clone. - Parry, C; Duong, N; Zhou, J; Mai, N; Diep, T; Thinh, L; Wain, J; Van Vinh Chau, N; Griffiths, D; Day, N; White, N; Hien, T; et al. (2002)
Surveillance for Streptococcus pneumoniae resistant to penicillin and other antimicrobial agents is necessary to define the optimal empirical antibiotic therapy for meningitis in resource-poor countries such as Vietnam. The clinical and microbiological features of 100 patients admitted to the Centre for Tropical Diseases in Ho Chi Minh City, Vietnam, between 1993 and 2002 with invasive pneumococcal disease were studied. A penicillin-nonsusceptible pneumococcus (MIC, > or =0.1 micro g/ml) was isolated from the blood or cerebrospinal fluid of 8% of patients (2 of 24) between 1993 and 1995 but 56% (20 of 36) during 1999 to 2002 (P < 0.0001). Pneumococcal isolates resistant to penicillin (MIC, > or =2.0 micro g/ml) increased from 0% (0 of 24) to 28% (10 of 36) (P = 0.002). Only one isolate was ceftriaxone resistant (MIC, 2.0 micro g/ml). Penicillin-nonsusceptible pneumococci were isolated from 78% of children younger than 15 years (28 of 36) compared with 25% of adults (16 of 64) (P = 0.0001). Isolation of a penicillin-nonsusceptible pneumococcus in adults with meningitis was independently associated with referral from another hospital (P = 0.005) and previous antibiotic therapy (P = 0.025). Multilocus sequence typing showed that 86% of the invasive penicillin-resistant pneumococcus isolates tested (12 of 14) were of the Spain(23F)-1 clone. The serotypes of >95% of the penicillin-nonsusceptible pneumococci were included in the currently available pneumococcal vaccines. Our findings point to the recent introduction and spread of the Spain(23F)-1 clone of penicillin-resistant pneumococci in Vietnam. Simple clinical predictors can be used to guide empirical antibiotic therapy of meningitis. Pneumococcal vaccination may help to control this problem.